2022
DOI: 10.3389/fpls.2021.769855
|View full text |Cite
|
Sign up to set email alerts
|

Vacuolar Processing Enzymes Modulating Susceptibility Response to Fusarium oxysporum f. sp. cubense Tropical Race 4 Infections in Banana

Abstract: Fusarium oxysporum f. sp. cubense tropical race 4 (FocTR4) is a destructive necrotrophic fungal pathogen afflicting global banana production. Infection process involves the activation of programmed cell death (PCD). In this study, seven Musa acuminata vacuolar processing enzyme (MaVPE1–MaVPE7) genes associated with PCD were successfully identified. Phylogenetic analysis and tissue-specific expression categorized these MaVPEs into the seed and vegetative types. FocTR4 infection induced the majority of MaVPE exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 69 publications
(101 reference statements)
0
7
0
Order By: Relevance
“…The resulting cDNA was analysed by qRT-PCR using QuantiNova SYBR Green PCR Kit (Qiagen, Germany) in Bio-rad CFX 96™ thermal cycler (Bio-Rad, USA) following the protocol described by Kamarudin et al 50 . The housekeeping glyceraldehyde 3-phosphate dehydrogenase ( gapdh ) and ubiquitin ( ubq ) genes were used as reference genes 51 . The data was analysed using Bio-rad CFX Manager™ software.…”
Section: Methodsmentioning
confidence: 99%
“…The resulting cDNA was analysed by qRT-PCR using QuantiNova SYBR Green PCR Kit (Qiagen, Germany) in Bio-rad CFX 96™ thermal cycler (Bio-Rad, USA) following the protocol described by Kamarudin et al 50 . The housekeeping glyceraldehyde 3-phosphate dehydrogenase ( gapdh ) and ubiquitin ( ubq ) genes were used as reference genes 51 . The data was analysed using Bio-rad CFX Manager™ software.…”
Section: Methodsmentioning
confidence: 99%
“…Total RNA was isolated via RNeasy Plant Mini Kit (Qiagen, Hilden, Germany) following the protocol described in [ 14 ]. First-strand cDNA was converted from 1 μg of the isolated total RNA using QuantiNova Reverse Transcription Kit (Qiagen, Germany).…”
Section: Methodsmentioning
confidence: 99%
“…These ultrastructural analyses have shown the contribution of VPEs to vacuole collapse during PCD [ 35 ]. Further research has shown that VPEs are involved in plant defense against such pathogens as the bacterium Erwinia amylovora [ 62 ], nematode Heterodera filipjevi [ 63 ], the oomycetes Hyaloperonospora arabidopsidis [ 64 ] and Phytophthora parasitica [ 65 ], and the fungi Phaeoisariopsis personata [ 66 ], Fusarium oxysporum (FocTR4) [ 67 ] and Botryosphaeria dothidea [ 68 ].…”
Section: Role Of Vpes In Pcd Under Biotic Stressmentioning
confidence: 99%